If p and q are the roots of x 2 − 2 x + A = 0 and
r and s are the roots of x 2 − 1 8 x + B = 0 such that p < q < r < s and p , q , r , s are in A.P, find ( A + B )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For those terms in AP, an easy way is to just substitute those ters as a − 3 d , a − d , a + d , a + 3 d . So that their sum directly gives us a . and we can easily find d
Log in to reply
in my mind at that moment the above written AP came so i used that
Log in to reply
The sequence I gave is too in AP. But its very easy to deal with these type of generalization.
I agree.. that's how I solved it :D
Did the same way.
Using Vieta's formulas, we get:
p + q = 2 r + s = 1 8
Using the formula for sum in an arithmetic series;
S n = 2 n ( 2 a + ( n + 1 ) d )
We get two linear equations;
2 2 ( 2 p + ( 2 − 1 ) d ) = 2 2 p + d = 2 ⟶ ( 1 ) S 4 − S 2 = 1 8 2 4 ( 2 p + ( 4 − 1 ) d ) − 2 = 1 8 2 p + 3 d = 1 0 ⟶ ( 2 )
Solving them simultaneously gives us
p = − 1 d = 4
Which is enough to complete the sequence;
. . . . p , q , r , s . . . . . . . . − 1 , 3 , 7 , 1 1 . . . .
Now return to Vieta's formula again to get
p . q = A r . s = B
Compute to get answer;
A = − 3 B = 7 7 ∴ A + B = 7 4
Given p,q,r,s is an AP. Let d be the common difference. Now consider p+q, r+s as another AP,. Now as per properties of AP, the new common difference will be four times the before, that is 4d. By writing roots of quadratic equations we will get p+q, p-q, r+s, r-s, and by applying properties of AP, we can find out the A+B value....
Problem Loading...
Note Loading...
Set Loading...
let p , q , r , s have common difference d so p , q , r , s can be written as p , p + d , p + 2 d , p + 3 d now using vieta's formulas we get − 2 = p + p + d and − 1 8 = p + 2 d + p + 3 d after eliminating these two equations just plug in the values of p , d so we get AP − 1 , 3 , 7 , 1 1 since A = p q and B = r s so using the above AP and values of p , q , r , s we get the answer 7 4